Hero or Villain: The Paradox of AI Algorithmic Disclosure in Utilitarian Versus Deontological Ethics - Woo Jin Kim; Yuhosua Ryoo; Eunjin Anna Kim; Marla Stafford (International Telecommunications Society (ITS), 2024)
Artificial intelligence (AI) already permeates various aspects of our daily lives, with applications ranging from recommendation systems and autonomous vehicles to personal home assistants and educational support systems (Kaur et al., 2020). These AI systems meet many of our personal needs while also affecting different areas of our social interactions. Additionally, AI technologies are highly effective in several key areas, enabling them to promote prosocial behaviors and enhance social welfare (Efthymiou & Hildebrand 2023). First, AI can be programmed to make decisions free from the biases that typically affect human judgment, promoting fairer and more equitable outcomes (Lin et al., 2021). Thus, AI can help allocate resources efficiently, maximizing impact without the influence of personal biases that might sway human donors or organizations (Landers & Behrend, 2023). Moreover, the constant availability and scalability of AI make it ideal for addressing large-scale social challenges such as managing disaster responses or optimizing resource distribution during crises (Sun et al., 2020). By integrating these capabilities, AI not only supports individual well-being but also bolsters collective welfare through the promotion of ethical and efficient solutions to complex social issues.
Keywords: 330; AI algorithmic disclosure; AI message type; Self-efficacy; Empathy